2017
DOI: 10.1210/jc.2016-3989
|View full text |Cite
|
Sign up to set email alerts
|

11-Oxygenated Androgens Are Biomarkers of Adrenal Volume and Testicular Adrenal Rest Tumors in 21-Hydroxylase Deficiency

Abstract: Context:Patients with 21-hydroxylase deficiency (21OHD) have long-term complications, resulting from poor disease control and/or glucocorticoid overtreatment. Lack of optimal biomarkers has made it challenging to tailor therapy and predict long-term outcomes.Objective:To identify biomarkers of disease control and long-term complications in 21OHD.Setting and Participants:Cross-sectional study of 114 patients (70 males), ages 2 to 67 years (median, 15 years), seen in a tertiary referral center.Methods:We correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 55 publications
6
70
2
Order By: Relevance
“…We recommend to include the evaluation of the AD/TS ratio in the regular follow-up of male patients with CAH and interpret this ratio in combination with gonadotropin concentrations in order to detect a disturbance of the HPG axis. Our study does not include data on 11-oxygenated androgens, that are generated through conversion of androstenedione and are reported to be elevated in patients with CAH (29,30). Recent studies indicate that 11-oxygenated androgens are almost entirely derived from the 11beta-hydroxylation of androstenedione in the adrenal, and as they are potent androgens, they can contribute to suppression of the HPG axis (31).…”
Section: Discussionmentioning
confidence: 96%
“…We recommend to include the evaluation of the AD/TS ratio in the regular follow-up of male patients with CAH and interpret this ratio in combination with gonadotropin concentrations in order to detect a disturbance of the HPG axis. Our study does not include data on 11-oxygenated androgens, that are generated through conversion of androstenedione and are reported to be elevated in patients with CAH (29,30). Recent studies indicate that 11-oxygenated androgens are almost entirely derived from the 11beta-hydroxylation of androstenedione in the adrenal, and as they are potent androgens, they can contribute to suppression of the HPG axis (31).…”
Section: Discussionmentioning
confidence: 96%
“…Functional analysis and KEGG pathway analysis highlight the adrenal steroidogenic properties of TART. Previous research indicated that TART produces adrenal-specific steroids (26,29), as blood of CAH patients with TART present higher levels of adrenal specific 11-oxygenated androgens compared to blood of patients without TART (29). Furthermore, higher levels of adrenal-specific steroid hormones have been detected in spermatic vein sampling compared to peripheral blood samples in CAH patients (16,26,30).…”
Section: Discussionmentioning
confidence: 96%
“…At least annual physical examination and hormone measurements (morning 17OHP and androstenedione) are recommended by the Endocrine Society, but no guidance is given about specific targets (9). Recently, metabolites such as 11-oxygenated-C 19 and pregnenolone sulphate have been suggested as useful biomarkers in classic CAH for disease control and long-term complications (92). However, these are not available in clinical practice and their use in NCAH has not been investigated.…”
Section: Treatment Evaluationmentioning
confidence: 99%